Development of Teaching Factory Learning Model in Industrial Automation in Vocational High Schools - Hatmojo, Yuwono Indro; Ikhsannudin, Wahyu (Jurnal Edukasi Elektro, 2024)
Vocational High Schools, as schools that aim to prepare students for work in a particular field, need effectiveness in the learning process. Its effectiveness must follow the real conditions required by the industry. With the rapid devel-opment of industry, industry-based learning, often called "Teaching Factory," is one of the right role models of learning. The type of research to be carried out is development research. The purpose of this study is to determine (1) the devel-opment of the teaching factory learning model, (2) the application of the teach-ing factory learning model, (3) user response to the product, and (4) the effec-tiveness of using the developed product. The development model used in this study is the Plomp development model. The Plomp development model includes (1) the initial investigation phase, (2) the design phase, (3) the realiza-tion/construction phase, (4) the testing, evaluation, and revision phase, and (5) the field test/implementation phase. Validity by model experts about the teach-ing factory learning model gets an average score of 95.45 and is included in the very decent category. The material expert gave it a score of 93.41, and it be-longs to the very decent category. The media expert gave it a score of 95.84, which belongs to the decent category. The effectiveness test result shows a sig-nificant difference between the learning outcomes in the Industrial Automation Engineering Expertise Concentration subjects before and after applying the Teaching Factory learning model. This shows the positive influence and effectiveness of using the Teaching Factory learning model on the learning out-comes of the Industrial Automation Engineering Expertise Concentration in In-dustrial Automation Engineering Vocational School students.